Tangible and Intangible Factors Affecting the Organizational Performance of Remote Health Workers - Suriyanti, Suriyanti; Azlan, Shakira Noor (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
The poor performance of local health workers in Indonesia has often been voiced in the regional health facility. This study investigates whether the bureaucratic behaviour, facilities and infrastructure, and organizational culture will increase local health workers’ motivation and job performance. This study collects data from 22 local health facilities across Maros Regency, Indonesia, for a quantitative investigation. A response rate of 294 samples is obtained following the normal distribution sampling. The data is then analyzed using the covariance-based Structural Equation Model (CB-SEM) with AMOS software. The results indicate that only facilities, infrastructures, and cultures are crucial for increasing health-worker motivation and job performance. The direct and mediating effects are also reported, with the results discussed with the following implication.